REVOLUTIONIZING ORDER MANAGEMENT THROUGH MOBILE ANALYTICS: A DATA-DRIVEN ANALYSIS OF IMPLEMENTATION IMPACT IN RETAIL AND TRANSPORTATION - Sai Krishna Paladugu, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a detailed analysis of mobile app implementation impact in order management across retail and transportation sectors, based on data collected from 250 companies over a 24-month period during 2023-2024. The article reveals significant improvements in key operational metrics, including a 47% enhancement in order fulfillment accuracy, 38% reduction in delivery delays, and 42% increase in customer satisfaction scores. Implementation of mobile analytics solutions demonstrates exceptional ROI, averaging 285% over three years, with particularly strong performance in real-time tracking capabilities achieving 99.9% accuracy. The article highlights substantial operational cost reductions of 38% through implementation of AI-powered optimization algorithms achieving 96.5% predictive modeling accuracy. In the transportation sector, fleet management optimization resulted in 32% route efficiency improvements and 24% fuel reduction, while retail operations saw inventory accuracy increase from 82.3% to 94.8%. The article also reveals that organizations leveraging these solutions experienced a 72% reduction in order processing time, 88% improvement in inventory accuracy, and 95% enhancement in customer satisfaction metrics. These findings establish mobile analytics as a crucial tool for modern order management, providing substantial business value and competitive advantage in the digital marketplace.